“Kandahar”: The silenced cry of women in Afghanistan - Yolanda García Ruiz (Cuadernos Electrónicos de Filosofía del Derecho, 2023)
The work analyzes the violation of women's rights in Afghanistan since the return of the Taliban to power in August 2021. The use of cinema to reflect on the situation suffered by Afghan women and girls because of religious fundamentalism has given us led to propose a commented review of the film "Kandahar" by the Iranian director Mohsen Makhmalbaf which premiered in 2001.